Phytophenols as Promoieties for Prodrug Design - Dhokchawle, Bharat V.; Mishra, Punit S.; Daniel, Renny J. (Current Drug Discovery Technologies, 2025)
One lucrative method for overcoming challenges in drug discovery or for enhancing undesirable properties of already-approved medications is prodrug design. The goal of this review is to present researchers with a profile of naturally occurring Phytophenols as carriers that would be used for prodrug synthesis as well as their advantages. Phytophenols offer several advantages when used as promoieties as they also possess antioxidant and analgesic properties, they are obtained naturally and their safety profile is well established. Several phytophenols like menthol, thymol, eugenol, guaiacol, sesamol, vanillin, and umbelliferone are some of the phytophenols having several beneficial properties and are extensively employed in the field of food processing and medicine. In the current review, we have listed all types of promoieties that are used for prodrug synthesis and phytophenols are reviewed, which may help researchers to select phytophenols based on their need and suitability for drug candidates.
Keywords: phytophenols